﻿Study of the influence of armed conflict on the reimbursement of oral glucose lowering drugs in Ukraine - Iryna Vlasenko; Lena Davtian (Pensoft Publishers, 2023)
The humanitarian crisis significantly affects the provision of medical and pharmaceutical care to PWD, and makes it difficult to predict its availability and affordability. It was established that despite the military actions in Ukraine, the reimbursement system is experiencing both negative and positive trends. Negative trends are : an increase in drug prices, the amount of patient co-payments, and a decrease in the number of glucose-lowering drugs that are subject to full reimbursement. Positive trends are: an increase in the amount of reimbursement and the number of glucose-lowering drugs that are included in the system reimbursements, including at the expense of extended dosage forms. The analysis showed that the war led to the introduction of positive changes - to increase the number of glucose-lowering drugs that are subject to full compensation.